2021
DOI: 10.1002/cyto.b.22046
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of myelodysplasia: Pre‐analytical and technical issues—Recommendations from the European LeukemiaNet

Abstract: Background: Flow cytometry (FCM) aids the diagnosis and prognostic stratification of patients with suspected or confirmed myelodysplastic syndrome (MDS). Over the past few years, significant progress has been made in the FCM field concerning technical issues (including software and hardware) and pre-analytical procedures.Methods: Recommendations are made based on the data and expert discussions generated from 13 yearly meetings of the European LeukemiaNet international MDS Flow working group. Results:We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 65 publications
1
28
0
Order By: Relevance
“…That said, the MyP count is probably the single most common flow test applied on bone marrow samples sent for myelodysplasia work‐up, as it is performed also in flow laboratories that do not yet carry out full MDS scoring. Therefore, while important pre‐analytical guidelines are available for MDS FC analysis (van der Velden et al, 2021) a fully standardized approach that covers all processing steps for MyP is count is unlikely to be universally applied in the near future. We, therefore, wanted to understand what the reproducibility of this key parameter is at the analytical level.…”
Section: Introductionmentioning
confidence: 99%
“…That said, the MyP count is probably the single most common flow test applied on bone marrow samples sent for myelodysplasia work‐up, as it is performed also in flow laboratories that do not yet carry out full MDS scoring. Therefore, while important pre‐analytical guidelines are available for MDS FC analysis (van der Velden et al, 2021) a fully standardized approach that covers all processing steps for MyP is count is unlikely to be universally applied in the near future. We, therefore, wanted to understand what the reproducibility of this key parameter is at the analytical level.…”
Section: Introductionmentioning
confidence: 99%
“…The MDS‐ and AML‐associated lowered expression patterns of pS6, pCREB, and pIκB α may suggest an altered MAPK signaling in HSPC of myeloid neoplasms as all these proteins are regulated by MAPK‐activated protein kinase‐1 (Frödin & Gammeltoft, 1999). We acquired samples using highly standardized bio‐banking procedures and according to recommendations with regard to the stability of marker expression during laboratory procedures (Velden et al, 2021), however, especially cell signaling markers may be sensitive to environmental conditions and therefore the above findings and their possible role in the pathobiology of MDS and secondary AML require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric analysis following ELN recommendations (Porwit et al, 2014 ; Porwit et al, 2022 ; van der Velden et al, 2023 ) demonstrated an expanded myeloid progenitor population (14% of total BM cells) with several abnormalities, including lack of CD13, HLA‐DR and myeloperoxidase (MPO) expression (Figure 1c–f ), a decreased fraction of B cell precursors within the CD34+ compartment, aberrant ratio of CD45 expression of lymphocytes vs. that of the myeloid progenitors (mean fluorescence intensity) and decreased sideward light scatter (SSC) of granulocytic cells (as ratio to lymphocyte SSC). These last three parameters and the percentage of CD34 + myeloid progenitors (among nucleated cells) comprise the Ogata score.…”
Section: Case 1 Detection Of An Aberrant Myeloid Blast Population In ...mentioning
confidence: 99%